SOME INTEGRAL FORMULAS FOR CLOSED MINIMALLY IMMERSED HYPERSURFACE IN THE UNIT SPHERE Sn+1 - Kulahci, Mihriban; Ergut, Mahmut (Inst Applied Mathematics, 2010)
In this paper, we obtain some integral formulas for minimal hypersurfaces in the unit sphere Sn+1.
Keywords: Clifford Torus; minimal hypersurfaces; ricci curvature; scalar curvature